Analytical approximation of transit time scattering due to magnetosonic waves. Issue 5 (13th March 2015) - Bortnik, J.; Thorne, R. M.; Ni, B.; Li, J.
Abstract: Recent test particle simulations have shown that energetic electrons traveling through fast magnetosonic (MS) wave packets can experience an effect which is specifically associated with the tight equatorial confinement of these waves, known as transit time scattering. However, such test particle simulations can be computationally cumbersome and offer limited insight into the dominant physical processes controlling the wave‐particle interactions, that is, in determining the effects of the various wave parameters and equatorial confinement on the particle scattering. In this paper, we show that such nonresonant effects can be effectively captured with a straightforward analytical treatment that is made possible with a set of reasonable, simplifying assumptions. It is shown that the effect of the wave confinement, which is not captured by the standard quasi‐linear theory approach, acts in such a way as to broaden the range of particle energies and pitch angles that can effectively resonate with the wave. The resulting diffusion coefficients can be readily incorporated into global diffusion models in order to test the effects of transit time scattering on the dynamical evolution of radiation belt fluxes. Key Points: New analytical expressions have been derived for magnetosonic waves scattering The diffusion coefficients contain nonresonant/transit time scattering effects These coefficients can be directly incorporated into global diffusion codes